Study of the polyphenolic compounds accumulation in Thymus serpyllum L. herb during the flowering period - О. V. Mazulin; L. А. Fukleva; G. V. Mazulin (The State Expert Center of the Ministry of Health of Ukraine, 2023)
The Thymus serpyllum L. is a widespread in the steppe bioсenosеs of southern and eastern Ukraine. It is well cultivated in specialized farms. A promising direction of modern phytochemical research of wild and cultivated Thymus L. species is the determination of the accumulation of biologically active polyphenolic compounds that exhibit pronounced biological activity. The purpose of the work is to determine the accumulation of polyphenolic compounds in Thymus serpyllum L. herb at the flowering using TLC and HPLC methods. The Thymus serpyllum L. herb was harvested in steppe biocenoses of southern and eastern Ukraine at the flowering, during the period of biologically active polyphenolic compounds maximum accumulation. For experimental studies, alcohol extracts from Thymus serpyllum L. herb (1:100) were used. The substances component composition was studied by TLC method Biostep CD 60 densitometer (Germany) and HPLC Agilent 1260 Infinity HPLC System Open LABCDS Software (Japan). TLC and HPLC methods revealed up to 25 polyphenolic compounds. Experimentally were determined 13 flavonoids and 12 hydroxycinnamic acids. All these biologically active compounds are well known in modern phytotherapy for their pronounced antimicrobial, anti-inflammatory and antioxidant activity. During the flowering period up to 25 polyphenolic compounds were identified and quantified in the ethanolic extract (1:100) obtained from Thymus serpyllum L. herbal raw material. Of these, 13 compounds were attributed to flavonoids with a defined total content (0.3 mg/100 mg) and 12 to hydroxycinnamic acids (0.9 mg/100 mg). The highest accumulation of hydroxycinnamic acids in the Thymus serpyllum L. herbal raw material were characterized by rosmarinic acid (12.77 + 1.19%), chlorogenic acid (8.55 + 0.79%) and p-coumaric acid (7.41 + 0.69%). Of flavonoids, the highest content were established for rutin (8.45 + 0.79%), luteolin (3.87 + 0.37%), luteolin-7-O-β-D-glucopyranoside (3.86 ± 0.33%), apigenin-7,4'-diglucoside (3.86 ± 0.32%), quercetin (3.85 ± 0.34%) and apigenin (3.81 ± 0.36%). The results obtained by TLC and HPLC methods indicate the perspective of polyphenolic compounds research for the purpose of determining the biological activity of extracts and carrying out the standardization of Thymus serpyllum L. herb. The study of the polyphenolic compounds accumulation in the Thymus serpyllum L. plant raw materials is important for this standardization and obtaining effective phytopreparations.